Transformational Leadership and Teacher Instructional Quality: A Study at SMPN 5 Satap Bungoro, Pangkep Regency - Afdalia Afdalia; Rahmawati Rahmawati; Saripuddin Saripuddin; Suarlin Suarlin (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study investigates the role of transformational leadership of school principals in enhancing the instructional quality of teachers at SMP Negeri 5 Satap Bungoro, Pangkep Regency, Indonesia. The research addresses three main problems: (1) how the principal's transformational leadership contributes to improving teacher performance in the classroom, (2) what strategies or actions the principal undertakes to elevate instructional practices, and (3) what supporting and inhibiting factors influence the process. Using a qualitative approach, data were collected through interviews, observation, and documentation involving the school principal and five teachers. The data were analyzed through data reduction, data display, conclusion drawing, and triangulation techniques. The findings reveal that the principal's transformational leadership plays a critical role in instructional improvement, marked by five key practices: presenting an inspiring leadership vision, encouraging professional growth, providing support and empowerment to teachers, fostering a collaborative and inclusive school culture, and delivering constructive feedback and evaluation. The strategies employed include the integration of the Merdeka Curriculum, mentoring and coaching of teachers, and fostering pedagogical understanding. Supporting factors include well-organized school and classroom environments and cleanliness, while the primary obstacles consist of limited funding, inadequate facilities and infrastructure, and a lack of strong teacher collaboration. In conclusion, transformational leadership contributes significantly to teacher development and improved instructional quality, especially in schools facing resource limitations. The study emphasizes the need for proactive leadership to overcome structural barriers and support effective teaching and learning.